(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to study the impact of Newspaper Advertisement on consumer behaviour and identify the positive and negative influence of newspaper advertisements. The relevant information for this research was gathered from both main and secondary resources.